Towards a New Taxonomy of Pattern-Making in the Visuo-Spatial Domain in Early Childhood Based on Zygonic Theory and the Sounds of Intent Framework of Musical Development - Adam Ockelford; Sarah McCarthy; Sue Gifford; Helen Thouless; Sharon Kirk; Michael Thorpe (Music & Science)
Pattern identification is an important part of children's development in understanding both music and mathematics. However, a review of the literature indicates that no formal taxonomy of pattern-making in the visual domain exists, which potentially limits practitioners’ capacity to support children in improving their mathematical understanding. This paper seeks to redress this situation with a theoretical examination of whether visuo-spatial pattern-making in early childhood develops on the same trajectory as pattern-making in the auditory domain. The cognition of musical structure (which is based on repeating patterns) in childhood has been defined in zygonic theory and the subsequent Sounds of Intent framework. Prior observational studies of children with both neurotypical and non-typical development (i.e., Ockelford et al., 2011 ; Voyajolu, 2021 ) have confirmed this thinking. Drawing on the principles set out in zygonic theory and using the structure laid out in the Sounds of Intent framework, the researchers propose how to map the development of pattern understanding from the auditory domain onto the visuo-spatial domain. An algorithm is used to demonstrate the structural processing load for different pattern types, which allows the putative developmental stages of pattern-processing capacity to be plotted sequentially. As a future step, exploratory research with children is suggested to test these assumptions and further develop our understanding of the perception of patterns within and between the domains. It is anticipated that this work would support practitioners working with children to offer alternative strategies to support the development of pattern-making in mathematics.